Pelatihan dan Pendampingan Digital Marketing bagi Pelaku UMKM Abon Tongkol Dapur Bugis - Ita Purnama; Muhamad Rizalul Fikri; Muhaimin Muhaimin (Indo Publishing, 2025)
The global advancement of technology and the internet has created vast opportunities in the business world, particularly in the digital marketing sector. The MSME